2004
DOI: 10.1007/s00259-004-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

Time course of functional recovery after coronary artery bypass grafting surgery according to the preoperative reversibility of perfusion impairment on myocardial SPECT

Abstract: Ischaemic dysfunctional myocardium with reversible perfusion impairment tends to recover function earlier after revascularisation surgery than myocardium with a persistent decrease in perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The early functional recovery could be associated with improved hospital outcome and comparable long-term results. The early functional outcome could be considered as a surrogate prognostic marker, although an improvement could still happen late, especially in more severely injured myocardium (11)(12)(13)36). Our data suggested that a multimodality diagnostic strategy for viability detection might provide complementary information for decision making in certain cases that are most likely to benefit from surgical revascularization.…”
Section: Early Functional Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The early functional recovery could be associated with improved hospital outcome and comparable long-term results. The early functional outcome could be considered as a surrogate prognostic marker, although an improvement could still happen late, especially in more severely injured myocardium (11)(12)(13)36). Our data suggested that a multimodality diagnostic strategy for viability detection might provide complementary information for decision making in certain cases that are most likely to benefit from surgical revascularization.…”
Section: Early Functional Outcomementioning
confidence: 99%
“…However, not all patients with ischemic cardiomyopathy recover in function after successful revascularization, despite the presence of viable myocardium identified using various noninvasive imaging techniques (4)(5)(6)(7)(8)(9)(10). The functional outcome and temporal variations could reflect the pathophysiologic mechanism of the dysfunction (11,12). Patients with early functional recovery could have a shorter hospital stay, a lower early postoperative morbidity and mortality, and, possibly, a better longterm functional outcome.…”
mentioning
confidence: 99%
“…Firstly, some segments may require a much longer time to functionally recover. It was shown that most of the hibernating segments improved their function 14 months after surgical revascularization [7], and other evidence shows that a significant proportion of segments require 16-24 months after CABG to reach functional recovery [13,22]. In our patients, the largest improvement of LVEF was observed at 12 months after CABG within the responder group; the LVEF improved from 33.8% at baseline to 44.3% at 12 months, with a subsequent slight decline to 41.2% at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Trials using MRI published to date have mostly evaluated the short-term left ventricular segmental functional improvement, within a few months of CABG (typically up to 6 months) [8][9][10][11][12][16][17][18][19][20][21]. However, it is known that the majority of hibernating segments may show functional recovery with a much longer delay of up to 14-24 months [7,13,22], so the previous trials may have missed these improvements. Furthermore, most of these trials focused on improvement of segmental function, and no distinct parameter was found to quantify the extent of viable myocardium necessary for significant LV reverse remodeling and ejection fraction improvement.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation